2021
DOI: 10.1021/acs.jced.0c00998
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibrium Measurements of Binary Systems of Dimethyl Carbonate with Dimethyl Sulfoxide, Anisole, and Diethyl Oxalate at 101.3 kPa

Abstract: In this work, three entrainers were selected to separate the azeotrope of dimethyl carbonate (DMC) and methanol, which were dimethyl sulfoxide, anisole, and diethyl oxalate. The vapor–liquid equilibrium (VLE) data of four binary systems (DMC + dimethyl sulfoxide, DMC + anisole, DMC + diethyl oxalate, and methanol + diethyl oxalate) were measured using a modified Rose-type circulating still at 101.3 kPa. The Van Ness point-to-point test and infinite dilution test were used to test the thermodynamic consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…To check the consistency of the measured VLE data, the Van Ness test and infinite dilution test are adopted with reference to our previous work. 20 The details of the methods are presented in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To check the consistency of the measured VLE data, the Van Ness test and infinite dilution test are adopted with reference to our previous work. 20 The details of the methods are presented in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous work, 20 the experimental VLE data was correlated with the NRTL and UNIQUAC models. The structural parameters r and q of ethylene glycol for the UNIQUAC model can be taken from the Aspen Property Databank, which are 2.4087 and 2.248, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VLE data for some binary mixtures consisting of either DMC or anisole with other components have been reported. 9−17 Recently, Song et al 18 have reported isobaric VLE data for the binary mixtures of DMC + dimethyl sulfoxide, DMC + anisole, DMC + diethyl oxalate, and methanol + diethyl oxalate at 101.3 kPa. However, for the binary system of DMC−anisole, isobaric, VLE data have not been reported Therefore, in the present study, we have considered DMC + anisole to study its phase equilibrium behavior at different pressures of 33.33, 46.66, 59.99, 73.33, and 94.66 kPa.…”
Section: Introductionmentioning
confidence: 99%